O reino encantado do sertão: uma crítica da produção e do fechamento da representação do sertão no romance de Ariano Suassuna - Martins, Jossefrânia Vieira (2011)
Based on the relation history, literature and space, this work examines the production and the closing of the representation of the hinterland in the Romance d A Pedra do Reino of the paraiban writer Ariano Suassuna. Inspired by method proposed by deconstructionist by Jacques Derrida, our reflection decomposes the writing scene of Suassuna by means of it s tracks to interpret the operation of the representation of the space-hinterland for the speech of the writer. Being thus, we present the elements chosen for Suassuna to weave an identification it s with this space-hinterland, taking a priori as a sentimental place and of familiar origin . The construction of this relation of belonging in great is measured grounded for a familiar memory entangled in the context politician who culminated in the Revolution of 1930 and that he resulted for the writer in the death of father. Suassuna launches a look on the identity and the Brazilian culture that guided in the tradition concept it searchs to deny the gift grounding its speech in the return to the past, a past order . Specifically in it s romance we notice to exist the fusing of these tracks in the production of a representation of the hinterland that it intends to close a concept of this space and its culture. Soon, the idea of kingdom sends to the space of the enchantments manufactured in infancy and retaken by the intellectual radical who in the anxiety of honor the father figure, does not save efforts in constructing a space representation that, over all, either faithful the representation that it searchs to trace of proper itself. Under one it marks of universality , the hinterland-kingdom of Suassuna if discloses eurocentric in the measure where it perpetuates discurse the filiation of the European cultural traditions.